PENGGUNAAN ANALISIS TREND DALAM MENILAI KINERJA KEUANGAN PT ALFA ENERGI INVESTAMA TBK TAHUN 2018-2020 - Sherly Herlina Mirta; Hari Sulistiyo (STIE PGRI Dewantara Jombang, 2021)
The purpose of this study was to evaluate PT Alfa Energi Investama Tbk's financial performance utilizing trend analysis on the statement of financial position and income statement. The technical analysis in this study was conducted through a library study, in which data collection procedures were used to obtain documents or corporate reports connected to the concerns highlighted by the researcher. According to the findings of the author's estimates utilizing trend analysis in this study, PT Alfa Energi Investama Tbk's financial performance from 2018 to 2020 is still considered strong and healthy, despite losses in 2018. However, the company was able to rise and earn profits in 2019 and 2020, demonstrating that the company is still able to function and operate in such a way that the company's financial performance has improved and the company can be considered financially healthy.